Twisted aromatic backbone engineering enables high-performance anion exchange membranes for durable water electrolysis - Wenjing Li; Jinsheng Li; Pingxia Zhang; Wei Qi; Xue Wang; Feiyan An; Youze Zeng; Dong Pan; Rina Sa; Meiling Xiao; Wei Xing; Jianbing Zhu; et al. (Chemical Engineering Journal, 2026)

TRPV4/IP3R-1-mediated endothelial pyroptosis drives pulmonary microvascular endothelial permeability in endotoxin-induced acute lung injury - Shasha Liu; Shuan Dong; Lirong Gong; Jing Yang; Huayang Liu; Meiling Piao; Ya Wu; Huirong An; Li Zhang; Jianbo Yu (Inflammation Research, 2026)

Synergy of interfacial modification and sustained release in plant-derived nanoliposomes for enhanced pesticide efficacy and dose reduction - Zhongxiang Zhao; Xipeng Jiang; Meiling Yang; Juan Yang; Shujie Ma; Lili Dong; Fengyue Suo; Jingao Dong; Lihui Zhang (Journal of Environmental Chemical Engineering, 2026)

Interleukin-12 Supports Self-renewal Division of Mouse Hematopoietic Stem Cells in Polyvinyl Alcohol-Based Culture - Jinglei Zhai; Xialin Li; Meiling Yin; Sen Zhang; Xiaoming Liu; Lisha Wang; Nini Wang; Lin Wang; Hideo Ema; Fang Dong (Stem Cell Reviews and Reports, 2026)

Community characteristics and risks of disinfection residual bacteria (DRB) during intermittent chlorination of stored rainwater - Zhiwen Chen; Xiaobin Liao; Binxiong Hu; Ye Yang; Meiling Liu; Yingying Dong; Tao Li; Likun Lv; Mawuli Dzakpasu; Yuefeng Xie; Wendong Wang (Journal of Environmental Chemical Engineering, 2026)

Seasonal gut microbiota and functional dynamics in brittle star (Ophiothrix exigua) from the Yellow Sea, China - Md. Tariful Islam Fuad; Yue Dong; Zhong Li; Meiling Ge; S.M. Sharifuzzaman; Xiaoshou Liu; Xuelei Zhang; Qinzeng Xu (Marine Environmental Research, 2026)

Impact of Drought‐Flood Abrupt Alternation on Vegetation Productivity in Karst and Non‐Karst Regions of Southern China - Meiling Zheng; Jianyu Fu; Yan Jin; Yadong Ji; Shengkun Dong; Bingjun Liu (International Journal of Climatology, 2026)
Drought‐flood abrupt alternation (DFAA)—characterised by rapid transitions between drought and flood events—is an extreme compound natural hazard that threatens ecosystems, particularly in fragile environments such as karst regions. Soil moisture is a key indicator of surface hydrological processes, directly regulating vegetation growth and recovery. This study utilises the Standardised Soil Moisture Index (SSMI) to identify DFAA events and applies Granger causality analysis to reveal soil moisture‐vegetation interactions. The impact of DFAA on vegetation productivity is quantified, with a comparative analysis between karst and non‐karst regions in southern China. The results indicate that: (1) From 2000 to 2020, SSMI showed a significant upward trend. Drought‐to‐flood events were more frequent, intense, and longer in duration than flood‐to‐drought events. Both types of events also exhibited substantial spatial heterogeneity. (2) SSMI and NDVI were positively correlated, with the strongest correlation reaching 0.32 at a 60‐day lag. Bidirectional causality between SSMI and NDVI was predominant, affecting 49.24% of the study area. (3) Flood‐to‐drought events synergistically intensified drought–flood stress, whilst drought‐to‐flood events mitigated stress effects. Consequently, vegetation recovery was slower after flood‐to‐drought events, particularly in hydrologically vulnerable karst regions.

Application of soda residue based material in a vertical flow constructed wetland for the simultaneous removal of tetracycline and phosphorus from freshwater aquaculture effluent - Ye Yang; Binxiong Hu; Tao Li; Meiling Liu; Ahmed Omer Abdalrahim Mohamed; Yingying Dong; Mawuli Dzakpasu; Hang Li; Yingyue Wang; Wendong Wang (Journal of Environmental Chemical Engineering, 2025)

Grass-legume mixture optimizes soil new carbon sequestration by leveraging microbial necromass dynamics in a pear orchard - Qiao Xu; Yingdong Zhao; Meiling Xu; Jinlong Dong; Weiqin Yin; Jing Ma; Xiaozhi Wang (Agriculture, Ecosystems & Environment, 2025)

Drainage reorganization near the eastern margin of the Tibetan Plateau as a result of fluvial response to differential uplift enhanced by isostatic compensation - Qinhong Mo; Zhenbo Hu; David Bridgland; Menghao Li; Baotian Pan; Zijuan Dong; Xiaohua Li; Meiling Zhong; Renzhe Pan; Ningyi Li; Rob Westaway (Global and Planetary Change, 2025)

Impact of soil moisture depth variation on agricultural drought monitoring in karst and non-karst areas of southwest China: a case study of Yunnan Province - Meiling Zheng; Jianyu Fu; Yan Jin; Yadong Ji; Shengkun Dong; Bingjun Liu (CATENA, 2025)

Reorganization of antecedent rivers in response to the evolving landscape at the northeastern margin of the Tibetan Plateau - Baotian Pan; Zijuan Dong; Zhenbo Hu; David Bridgland; Qinhong Mo; Xiaohua Li; Menghao Li; Yanan Yang; Meiling Zhong; Renzhe Pan (Earth-Science Reviews, 2025)

Neural-network-based adaptive control for space manipulator system with actuator faults: a fully actuated system approach - Meiling Hu; Xuebo Yang; Hanlin Dong; Yimu Jiang (Advances in Space Research, 2025)

Copper oxide nanoparticles disrupt lysosomal function and promote foam cell formation in RAW264.7 macrophages - Yilin Luo; Kun Zhang; Lejiao Mao; Meiling Tan; Xiaomei Dong; Na Li; Yuexing Zhou; Chengzhi Chen; Zhen Zou; Jun Zhang (Toxicology, 2025)

Sensitive measurement of polycyclic aromatic hydrocarbons based on strong enrichment from magnetic covalent organic framework before high performance liquid chromatography analysis - Guangyu Dong; Liushan Jiang; Linchun Nie; Jiawei Liao; Xiaodie Geng; Wenjing Liu; Dejing Meng; Meiling Xu; Na Liu; Qingxiang Zhou; Chunmao Chen (Journal of Environmental Chemical Engineering, 2025)

Advanced treatment of coal to ethylene glycol industry wastewater by catalytic ozonation: Performance and mechanism - Yingying Dong; Lan Yang; Nan Zhang; Ningning Xiao; Yongxia Sun; Ye Yang; Meiling Liu; Zhiwen Chen; Jiangwei Wang; Wendong Wang (Journal of Water Process Engineering, 2025)

Acrylamide drives amidase-mediated gut dysbiosis to aggravate colitis - Daotong Li; Yinghua Luo; Huimin Fan; Li Dong; Xiaoying Zhang; Yu Feng; Meiling Tian; Shuqing Zhang; Wenjing Chen; Lujia Zhang; Jianwei Gao; Xiangning Ma; et al. (Science Bulletin, 2025)

Longitudinal relationship between built environment and physical fitness in Chinese children and adolescents: Findings from the COHERENCE study - Jinghong Liang; Shan Huang; Wenwen Bao; Yingqi Pu; Meiling Liu; Xiuzhi Yang; Zhuowen Wu; Jiaqi Chen; Guanghui Dong; Yajun Chen (Building and Environment, 2025)

Tectonic deformation and kinematics of fluvial terraces marking the northeastern margin of the Tibetan Plateau - Zijuan Dong; Baotian Pan; Zhenbo Hu; David Bridgland; Jun Wang; Rob Westaway; Menghao Li; Qinhong Mo; Xiaohua Li; Xilin Cao; Meiling Zhong; Renzhe Pan (Quaternary Science Reviews, 2024)

Genomic selection on ear height, plant height and grain yield in the primary testing stage of maize hybrids - Xinying Kong; Shuwen Ji; Yubo Liu; Xuecai Zhang; Meiling Liu; Chen Yue; Ruichen Yang; Cong Li; Xiaomei Dong; Ao Zhang; Yanye Ruan (Euphytica, 2024)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

The coupling between tectonic uplift and climate change recorded by the Yellow River terraces during the Zoige basin excavation in the northeastern Tibetan Plateau - Qinhong Mo; Zhenbo Hu; David Bridgland; Menghao Li; Baotian Pan; Ningyi Li; Zijuan Dong; Xiaohua Li; Yanan Yang; Meiling Zhong; Renzhe Pan; Rob Westaway (Geomorphology, 2024)

Phosphorylation of RasGRP1 by Shc3 prevents RasGRP1 degradation and contributes to Ras/c-Jun activation in hepatocellular carcinoma - Xinran Zhang; Yun Liu; Rui Yang; Yuanyuan Guo; Meiling Yan; Ying Xiao; Yunzhuo Dong; Ruixia Zhang; Yinpeng Qin; Yishan Bu; Yi Zhang; Huier Gao (Molecular and Cellular Biochemistry, 2024)

A Profile of Drug-Resistant Mutations in Mycobacterium tuberculosis Isolates from Guangdong Province, China - Chenchen Zhang; Zhuhua Wu; Xinchun Huang; Yuchuan Zhao; Qi Sun; Yanmei Chen; Huixin Guo; Qinghua Liao; Huizhong Wu; Xunxun Chen; Anqi Liang; Wenya Dong; et al. (Indian Journal of Microbiology, 2024)

A new method of alkalinity remediation for Cd-contaminated groundwater by PAAS-modified MgCO3/Mg(OH)2 colloid - Bowen Li; Meiling Tang; Peng Wang; Shibin Liu; Meng Yao; Jun Dong (Chemosphere, 2024)

Plio-Pleistocene drainage reorganization in the middle Yellow River of China, revealed by provenance and paleocurrent analysis of fluvial sediments - Menghao Li; Zhenbo Hu; Ping Wang; Baotian Pan; David Bridgland; Qinhong Mo; Xiaohua Li; Zijuan Dong; Meiling Zhong; Renzhe Pan; Ningyi Li (Geomorphology, 2024)

Microbial features with uranium pollution in artificial reservoir sediments at different depths under drought stress - Siyu Liu; Juan Liu; Jingye She; Zhenyu Xie; Lei Zhou; Qunwei Dai; Xing Zhang; Yuebing Wan; Meiling Yin; Xinjiao Dong; Min Zhao; Diyun Chen; et al. (Science of The Total Environment, 2024)

Thermo-responsive ion imprinted polymer on the surface of magnetic carbon nanospheres for recognizing and capturing low-concentration lithium ion - Chang Liang; Xiaopei Zhang; Weifeng Liu; Xingfu Song; Shuying Sun; Dongju Fu; Geng Dong; Meiling Wang; Yonghui Bai; Xuguang Liu (Minerals Engineering, 2023)

Aerogel-hydrogel biphase gels based on physically crosslinked β-lactoglobulin fibrils/polyvinyl alcohol for skin wound dressings: In vitro and in vivo characterization - Min Gong; Huanhuan Shi; Zuquan Hu; Fang Wang; Meiling Dong; Ronghua Lei; Zhu Zeng; Yun Wang; Jin Chen (Chemical Engineering Journal, 2023)

High mechanical CuO@stainless steel mesh for continuous and durable separation of surfactant-stabilized viscous and light/heavy-mixed oily emulsions in liter-scale - Qing He; Meiling Guo; Juan Shu; Hua Hu; Hongwei Su; Guilong Yan; Zhenyu Li; Li Wang; Dong Xiang; Chunxia Zhao; Yuanpeng Wu; Wei Wang; et al. (Journal of Water Process Engineering, 2023)

Characterisation of kapok fibre's biochar for arsenate adsorption removal from aqueous solution. - Kanfolo Franck Herve Yeo; Yingying Dong; Tongxuan Xue; Zhiwen Chen; Nan Zhang; Ye Yang; Liu Han; Meiling Liu; Ange Nsilani Kouediatouka; Hanse Pablick Patherny Lobo Mouguegue; Wendong Wang (Environmental Research, 2023)

Channel migration in the northeastern margin of the Tibetan Plateau and its implication for fluvial response to the interaction between rapid tectonic activity, climatic fluctuation and human influence - Baotian Pan; Xiaohua Li; Zhenbo Hu; David Bridgland; Qinhong Mo; Zijuan Dong; Menghao Li; Yanan Yang; Rob Westaway; Guanghui Dong; Shanjia Zhang; Meiling Zhong (Quaternary Science Reviews, 2023)

SUMO and PIAS repress NF-κB activation in a basal chordate - Shenghui Chen; Xianan Fu; Ruihua Wang; Mingshi Li; Xinyu Yan; Zirui Yue; Shang-Wu Chen; Meiling Dong; Anlong Xu; Shengfeng Huang (Fish & Shellfish Immunology, 2023)

Ferroptosis is involved in polymyxin B-induced acute kidney injury via activation of p53 - Hongyu Li; Boying Wang; Sheng Wu; Shuying Dong; Guojun Jiang; Yingying Huang; Xuhui Tong; Meiling Yu (Chemico-Biological Interactions, 2023)

Terminal sliding-mode control for input-constrained free-float space manipulator via learning-based adaptive uncertainty rejection - Meiling Hu; Xuebo Yang; Hanlin Dong (Advances in Space Research, 2023)

Self-intercepting interference of hydrogen-bond induced flexible hybrid film to facilitate lithium extraction - Meiling Wang; Tianyuan Zhang; Zhixiang Meng; Chongji Wang; Weikang Dong; Jijian Liu; Su Yang; Xudong Hou; Xiaoran Cheng; Weifeng Liu; Chenyang Xing; Xuguang Liu; et al. (Chemical Engineering Journal, 2023)

Isoliquiritigenin attenuates pathological cardiac hypertrophy via regulating AMPKα in vivo and in vitro - Meiling Gao; Qiang Cai; Haichao Si; Si Shi; Huixia Wei; Miaomiao Lv; Xiaofan Wang; Tieli Dong (Journal of Molecular Histology, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Investigation of Lactic Acid Bacteria Isolated from Giant Panda Feces for Potential Probiotics In Vitro - Qian Liu; Xueqin Ni; Qiang Wang; Zhirong Peng; Lili Niu; Meiling Xie; Yicen Lin; Yi Zhou; Hao Sun; Kangcheng Pan; Bo Jing; Dong Zeng (Probiotics and Antimicrobial Proteins, 2019)

Akt Inhibitor Perifosine Prevents Epileptogenesis in a Rat Model of Temporal Lobe Epilepsy - Feng Zhu; Jiejing Kai; Linglin Chen; Meiling Wu; Jingyin Dong; Qingmei Wang; Ling-Hui Zeng (Neuroscience Bulletin, 2018)

Triassic ore-bearing and barren porphyries in the Zhongdian Arc of SW China: implications for the subduction of the Palaeo-Tethys Ocean - Peng Wang; Guochen Dong; M. Santosh; Xuefeng Li; Meiling Dong (International Geology Review, 2017)

Dissecting the complex molecular evolution and expression of polygalacturonase gene family in Brassica rapa ssp. chinensis - Ying Liang; Youjian Yu; Xiuping Shen; Heng Dong; Meiling Lyu; Liai Xu; Zhiming Ma; Tingting Liu; Jiashu Cao (Plant Molecular Biology, 2015)

Allosteric therapies for lung cancer - Ye Ling; Meiling Jing; Xiang-dong Wang (Cancer and Metastasis Reviews, 2015)

Decreased TK activity alters growth, yield and tolerance to low temperature and low light intensity in transgenic cucumber plants - Huangai Bi; Xubing Dong; Guoxiu Wu; Meiling Wang; Xizhen Ai (Plant Cell Reports, 2015)

Analysis of ΔpH and the xanthophyll cycle in NPQ of the Antarctic sea ice alga Chlamydomonas sp. ICE-L - Shanli Mou; Xiaowen Zhang; Naihao Ye; Jinlai Miao; Shaona Cao; Dong Xu; Xiao Fan; Meiling An (Extremophiles, 2013)